Concepts of Small Business and Entrepreneurship, Their Essence and Content - Bakhritdinovich, Ismoilov Ravshanjon; Orifjanovich, Jamolov Gofirjon; Anvarovich, Sulaymonov Bekzod; Sadriddinovich, Omonov Soxibjon (European Journal of Life Safety and Stability (2660-9630), 2021)
This article provides ideas and feedback on the concepts of small business and entrepreneurship, their essence and content.